Learning curve for esophageal peroral endoscopic myotomy: a systematic review and meta-analysis - Puli, Srinivas R.; Wagh, Mihir S.; Forcione, David; Gopakumar, Harishankar (Endoscopy, 2022)
Background and study aims Peroral endoscopic myotomy (POEM) is a minimally invasive endoscopic procedure for the treatment of achalasia and certain spastic esophageal motility disorders, delivering excellent results in experienced hands. However, this complex and technically challenging procedure requires advanced endoscopic skills. The aim of this study was to conduct a systematic review and meta-analysis of current data to evaluate the learning curve for POEM in new adopters of this technique.Methods Electronic databases (PubMed, Embase, and Cochrane Library) from inception to November 2021 were searched for publications addressing the learning curve in POEM. Pooling was conducted by both fixed- and random-effects models. Secondary outcomes reviewed were clinical success defined by Eckardt score ≤ 3 when available and adverse events.Results Eight studies involving 1904 patients met the inclusion criteria. In the pooled analysis, new adopters of POEM attained proficiency at a mean of 24.67 procedures (95 %CI 23.93 to 25.41). Once proficiency was achieved, the pooled total procedure time plateaued at a mean of 85.38 minutes (95 %CI 81.48 to 89.28), the pooled mean procedure time per centimeter of myotomy was 6.25 minutes (95 %CI 5.69 to 6.82), and the pooled mean length of myotomy was 11.49 cm (95 %CI 10.90 to 12.08).Conclusions Our analysis showed that new adopters of POEM with previous advanced endoscopy experience required about 25 procedures to attain proficiency. The average time for each procedure once proficiency was attained was about 85 minutes.